Nasal cavities and the nasal septum: Anatomical variants and assessment of features with computed tomography - Cellina, Michaela (Neuroradiol J, 2020)
The nasal cavities are complex anatomical structures with high inter-individual variability that relates to different functions. Different anatomic variants may manifest at this site, mainly belonging to the nasal septum and turbinates. Precise knowledge of the anatomy and variants is fundamental for both radiologists and ENT surgeons. This article provides an overview of the main anatomic variants and their frequency, according to the existing literature, as well as ongoing research on nasal cavity segmentation in order to obtain personal 3D models and to predict post-surgical results.